Kecurangan Akuntansi Memediasi Pengaruh Sifat Machiavellian Pada Persepsi Creative Accounting - Prajnananira, I Gusti Ayu Dhira Yoseva; Susilowati, Endah (Universitas Gorontalo, 2023)
This research aims to investigate how accounting fraud mediates Machiavellian traits on the perception of creative accounting and the relationships among the variables. The data used is primary data obtained from questionnaires and processed using SmartPLS 4.0. The research results indicate that Machiavellian traits influence accounting fraud and the perception of creative accounting. Accounting fraud also affects the perception of creative accounting. Therefore, it can be said that accounting fraud serves as a mediator in moderating the influence of Machiavellian traits on the perception of creative accounting. The implication of this study is the enhancement of students' ethics by strengthening business ethics education.